Novel rGO-T-C(n) Nanosheets developed via click chemistry as a lubricant anti-wear additive - Bagheri, S.; Jamal, N.; Halilu, A.; TermehYousefi, A. (Nature Publishing Group, 2018)
Process equipment and facilities are constantly facing the dilemmas of tear and wear. This manuscript introducing functionalized reduced graphene oxide with triazole moiety via click chemistry as a anti-wear additive. While this has been achieved successfully, full characterization of the new anti-wear additive material revealed it to be promising in ameliorating issues of wears. One of the merits of the synthesized material includes reduction of contact asperity as the lipophilic alkyl chain length increases. It has been tested to be functional when formulated as an additive in group III petroleum base oil. Accordingly, it shows an irregularity in renewable base oil. Following screening evaluations of the lipophilic alkyl chain lengths, the additive with twelve carbon atoms; functionalized reduced graphene oxide, rGO-T-C(12) was confirmed to stand out among others with the good reduction of friction coefficient and the least wear scar diameter of ∼539.78 μm, compared to the base oil containing no additive.